METHODOLOGY OF USING INTERACTIVE METHODS IN DEVELOPING MATHEMATICAL CREATIVITY - Absoatov Ulugbek Kadirovich (Bright Mind Publishing, 2025)
This article scientifically reveals interactive methods and their effectiveness in developing mathematical creativity of high school students in the process of teaching mathematics.
Keywords: Mathematical creativity, brainstorming, group thinking, divergent thinking, strategic solutions, encouraging diversity of thought, competence.